2020
DOI: 10.1021/acs.jpca.0c05901
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Perspective about the Reaction Mechanism and H2 Production during the Combustion of Al Nanoparticles/H2O2 Bipropellants

Abstract: The combination of Al nanoparticles (ANPs) and hydrogen peroxide (H 2 O 2 ) can serve as environmentally friendly bipropellants and maximize the energetic benefits through harnessing heat release and chemical energy stored in H 2 . This work presents an atomic insight into the combustion mechanism of ANPs/H 2 O 2 . Two main paths, including the ANPs oxidation by H 2 O 2 to produce H 2 and Al oxides, and the catalytic decomposition of H 2 O 2 on ANP surface to generate O 2 and H 2 O, are confirmed to maintain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The force field has been successfully used to reveal the influence of carbon coatings on the oxidation of ANPs and the combustion reaction of ANPs with oxidizing agents (O 2 , H 2 O, H 2 O 2 , etc.) [49,50]. First, an Al particle with a diameter of 2.8 nm and 675 atoms was constructed.…”
Section: Model Constructionmentioning
confidence: 99%
“…The force field has been successfully used to reveal the influence of carbon coatings on the oxidation of ANPs and the combustion reaction of ANPs with oxidizing agents (O 2 , H 2 O, H 2 O 2 , etc.) [49,50]. First, an Al particle with a diameter of 2.8 nm and 675 atoms was constructed.…”
Section: Model Constructionmentioning
confidence: 99%
“…16 For H 2 O x (x = 1 or 2) molecules, both the dissociated H and O atoms diffuse into the ANPs, eventually producing H 2 and aluminum oxides. 17 Starik et al expanded the ignition and combustion study of ANPs to incorporate CH 4 in a mixture with O 2. 18 They found that the ignition delay and combustion efficiency of ANPs were ameliorated when compared to Al powder.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Meanwhile, various AlN chain products (AlN 4 , Al n N 2 n +2 , and AlN 3 O) are formed . For H 2 O x ( x = 1 or 2) molecules, both the dissociated H and O atoms diffuse into the ANPs, eventually producing H 2 and aluminum oxides . Starik et al expanded the ignition and combustion study of ANPs to incorporate CH 4 in a mixture with O 2.…”
Section: Introductionmentioning
confidence: 99%